Survey of ICT and Education in Africa : Tanzania Country Report - Hare, Harry (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The past few years witnessed a host of activities aimed at injecting ICT in Tanzania's education sector. From the International Institute for Communication and Development (IICD)-supported roundtable in Bagamoyo where 11 ICT for education projects were formulated to the Swedish International Development Agency (SIDA)-supported stakeholders forum of January 2005, which saw the birth of the Tanzania eSchools initiative and many other activities in between. All this has, as a result, tremendously increased the awareness of the benefits of ICT within the education sector, not to mention the support from several development partners. With the raised awareness the potential that ICT has demonstrated in improving the quality and access to education, the government, through the ministry of education and vocational training has recently developed an ICT Policy for basic education (July 2007) that will among other things, structure the adoption of ICT within the education sector.